Investigation of nanophase separation in IR optical glasses As₄₀Se₆₀ using resonant Raman scattering - Mateleshko, N.; Mitsa, V.; Veres, M.; Koos, M.; Stronski, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Resonant Raman spectra of stoichiometric glass (g) g-As₄₀Se₆₀ have been investigated. It was observed that the increasing of excitation radiation energy hv>E₀ (E₀ is pseudogap width) changes a shape, intensity, and position of Raman peaks of g-As₄₀Se₆₀. The structure and vibration spectra of some As-Se clusters were calculated applying the ab initio method. In order to elucidate structural features of g-As₄₀Se₆₀, we combined the experimental Raman data and theoretical calculations.